Effect etanol extract of senduduk leaves (melastoma malabathricum L.) On SGPT and SGOT levels in white rats induced with Monosodium Glutamate - Rahmadani, Nurul; Febriani, Husnarika; Hutasuhut, Melfa Aisyah (International Journal of Ecophysiology, 2025)
The use of Monosodium Glutamate (MSG) has caused a lot of controversy because people think that overuse of MSG may have adverse effects on health. Prolonged consumption of MSG and excessive amounts can cause an imbalance between antioxidants that will disrupt liver function characterised byeinicreased lievelseoif !iSer.um Gliutamic Oxialoacetic Train.saminasee (Si.G.OT) and Seirum Gilutamic PyiruvateeTra.nsiaminasee (SiG.PT) in the bloodstream. The negative effects of MSG can be prevented by reducing MSG consumption and utilising herbal plants such as senduduk leaves. This experiment wants to measure the effect of senduduk le.af e.xtract o.n the number o.f S.GPT and SGOT due to MSG. This study used experimental research for 14 days with 20 male white rats with 5 treatment groups. K- without treatment. K+ was given MSG 100 mg/kgBW (morning), P1, P2, and P3 were given MSG 100 m!g/kgBW (morning) and senduduk leaf extract (P1 = 150, P2 = 200, P3 = 250 m.gi./ .k.g BiW) (afternoon). Theestages inethisestudy include phytochemical screening, observation of hepatic morphology and observation of SGPT and SGOT levels. Blood collection through the orbital sinus. Data analysis used o.neewi.ay anio.va ain.d diu.ncan’sef.ur.th.er t.esit. The optimal dose to improve the amount of SGPT and SGOT due to MSG induction is group P3 wiith a d.os.eeoif 250 m.gi./ .kig BiW.